IDENTIFICATION OF BACTERIA THAT CAUSED FIRE BLIGHT ON PEAR AND APPLE IN NINEVEH GOVERNORATE AND IT’S CONTROL - Ahmed Saeed; Rasmia Omar Sultan (Mesopotamia Journal of Agriculture)
A field survey conducted in 2013 revealed the occurrence of Fire blight disease in the three surveyed areas (Nineveh agricultural station, Al-Rasheediya and Hawi Al-Kaneesa) in Nineveh Province. The highest infection rate was 88% for pear and apple trees in Hawi Al-Kaneesa while the infection degree was 0.61 and 0.43 degree respectively highest in Nineveh agricultural station for pear and apple trees. The pathogen was isolated from infected fruits, flowers and twigs, identified by many biochemical tests and confirmed by Agglutination test and Pathogenecity on pear seedlings and fruits. The results indicated that the isolated bacteria was Erwinia amylovora. The effect of three bactericides on the bacterial growth was tested in vitro the results indicated that ciprofloxacin was more effective than Cupprosate and Revanol.